2004
DOI: 10.1093/jjco/hyh015
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Percent Equol Producers between Prostate Cancer Patients and Controls: Case-controlled Studies of Isoflavones in Japanese, Korean and American Residents

Abstract: These results suggest that the ability of producing equol or equol itself is closely related to the lower incidence of prostate cancer. The results also suggest that a diet based on soybean isoflavones will be useful in preventing prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
157
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(181 citation statements)
references
References 7 publications
12
157
3
Order By: Relevance
“…The observation that 30% of our second-and third-generation subjects were equol producers agrees with published reports for Western populations (Lampe et al, 1998;Setchell et al, 2002;Frankenfeld et al, 2004). Our finding that the older generation women excreted more equol after a soy challenge than younger women is consistent with equol producer rates of 50-60% reported from Japan (Akaza et al, 2004;Ozasa et al, 2004). A significant higher prevalence of equol producers among Korean Americans than Caucasians (51 vs 36%; P ¼ 0.015) after a soy challenge also supports the idea that consumers of a traditional Asian diet metabolize isoflavones differently (Song et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The observation that 30% of our second-and third-generation subjects were equol producers agrees with published reports for Western populations (Lampe et al, 1998;Setchell et al, 2002;Frankenfeld et al, 2004). Our finding that the older generation women excreted more equol after a soy challenge than younger women is consistent with equol producer rates of 50-60% reported from Japan (Akaza et al, 2004;Ozasa et al, 2004). A significant higher prevalence of equol producers among Korean Americans than Caucasians (51 vs 36%; P ¼ 0.015) after a soy challenge also supports the idea that consumers of a traditional Asian diet metabolize isoflavones differently (Song et al, 2006).…”
Section: Discussionsupporting
confidence: 92%
“…The extent of the metabolism seems to be highly variable among individuals and may be influenced by other components of the diet (Lampe et al, 1999;Rowland et al, 2000). Approximately 30-50% of the human population produces equol (Setchell et al, 2002;Atkinson et al, 2005), but it appears that a greater proportion of Asian than Western populations have the ability to produce equol (Setchell et al, 2002;Akaza et al, 2004;Ozasa et al, 2004), possibly because they were exposed to soy early in life. Urinary isoflavonoid excretion serves as an excellent biomarker for soy intake owing to the rapid absorption and excretion of isoflavonoids specific to soy foods (Maskarinec et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Those studies of the serum equol level revealed two types of men with different metabolic patterns of daidzein to equol; one group is equol producers and the other is equol non-producers whose serum equol was under the detection level (0.5 ng ml À1 ), and the proportion of equol producers among patients with prostate cancer was significantly lower than that among the agematched control group patients. 18 Moreover, the proportion of equol producers was significantly lower among patients with poorly differentiated adenocarcinoma than among those with well or moderately differentiated adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the percentage of equol producers was very low (10%) in the Japanese teenager as well as in the American healthy men (14%) in contrast to the Japanese and Korean healthy men (46 and 59%, respectively) in the present study in our previous case-control study. 19 Unfortunately, we have no data on the intakes of isoflavones and proportion of equol producers in the old-age Japanese who ingested only traditional Japanese foods. Therefore, we cannot conclude whether the proportions of equol producers in the sixties and seventies (54 and 59%, respectively) were high or not when compared to the old-age Japanese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation